Subjective Positive and Negative Sleep Variables Differentially Affect Cellular Immune Activity in a Breast Cancer Survivor: A Time-series Analysis Approach - Singer, Magdalena; Burbaum, Christina; Fritzsche, Kurt; Peterlini, Sylvia; Bliem, Harald R.; Ocaña-Peinado, Francisco M.; Fuchs, Dietmar; Schubert, Christian (Frontiers in Neurology, 2018)
This study on a breast cancer survivor suffering from cancer-related fatigue and depression investigated the bidirectional relationship between cellular immune activity and subjective sleep. The 49-year-old patient (breast cancer diagnosis five years prior to the study, currently in remission) collected her full urine output for 28 days in 12-h intervals (8 p.m. to 8 a.m. and 8 a.m. to 8 p.m.). These urine samples were used to determine urinary neopterin (cellular immune activation marker) and creatinine concentrations via high pressure liquid chromatography (HPLC). Each morning, the patient answered questions on five sleep variables: sleep quality (SQ), sleep recreational value (SRV), total sleep time (TST), total wake time (TWT) and awakenings during sleep period (ADS). For the purpose of this study, the time series of the 28 nighttime urinary neopterin levels and the sleep variables were determined. Using Centered Moving Average (CMA) smoothing and cross-correlational analysis, this study showed that increases in the positive sleep variables SQ and SRV were followed by urinary neopterin concentration decreases after 96–120 h (SQ, lag 4: r = -0.411; p = 0.044; SRV: lag 4: r = -0.472; p = 0.021) and 120–144 h (SRV, lag 5: r = -0.464; p = 0.026). Increases in the negative sleep variable TWT, by contrast, were followed by increases in urinary neopterin concentrations 72–96 h later (lag 3: r = 0.522; p = 0.009). No systematic effects in the other direction, i.e. from urinary neopterin levels to sleep, were observed in this study. Though preliminary, the findings of this study highlight the benefit of carefully investigating temporal delays and directions of effects when studying the dynamic relationship between sleep and immune variables in the natural context of everyday life.